MANAJEMEN PROGRAM PENCEGAHAN SIFILIS DARI IBU KE ANAK - Susilawati Susilawati; Adinda Gusti Irawan (CV. ADIBA AISHA AMIRA, 2023)
Syphilis is an STI (sexually transmitted infection) which causes quite severe conditions, such as brain infection (neurosyphilis), bodily defects (guma). In the population of pregnant women who are infected with syphilis, if not treated adequately, it will cause 67% of pregnancies to end in abortion, stillbirth, or neonatal infection (congenital syphilis). The method used in this research is library research or library research. The Ministry of Health (Kemenkes) recorded 20,783 reported cases of syphilis infection in 2022. This number has increased significantly from the 2018 case reports which recorded 12,484 cases. Syphilis has also been reported to have increased in the last 5 years (2016- 2022). important in prevention, includes the management of the PPIA program which includes processes, planning, implementation, organizing, monitoring and evaluation as well as program recording and reporting. All of these processes are carried out at all levels in accordance with the authorities at each level